The Effect of Teacher Competence, Online Learning Model on Student's Learning Effectiveness at State Junior High School, Telaga District, Gorontalo Regency - Warni Tune Sumar; Sulkifly Sulkifly; Nina Lamatenggo; Intan Abdul Razak (JETL (Journal of Education, Teaching and Learning), 2022)
This study aims to determine the direct influence of teacher competence and online learning model on students’ learning effectiveness. It employs a survey method by applying a questionnaire. In addition, data analysis uses descriptive and inferential analysis with path analysis. The population in this study is the whole students at Grade VIII of State Junior High School throughout Telaga Subdistrict, Gorontalo Regency, in the amount of 158 students. At the same time, the samples are 88 students taken by using a proportionate stratified sampling technique. Research findings reveal that: 1) teacher competence has a direct positive influence on students’ learning effectiveness, 2) online learning model has a direct positive influence on students’ learning effectiveness, 3) teacher competence and online learning model simultaneously influence students’ learning effectiveness. As having been stated previously, the purpose of this study is to find out the influence of teacher competence and online learning model towards students’ learning effectiveness at State Junior High School throughout Telaga Subdistrict, Gorontalo Regency. High-quality education can produce quality and productive human resources so that they can compete in the competitive era of globalization. Importantly, students’ learning outcomes are a benchmark of success in learning the material. Teachers need to evaluate students’ abilities in order to figure out student learning outcomes. In other words, student learning outcomes can be perceptible from the result of the evaluation.